Strategic Role Identification Of Agro-Science Technopark Management In Gorontalo Province - Wawan K. Tolinggi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study aims at determining strategic role groups related to the management of agro-science technopark site based on external conditions (opportunities and threats) and internal condition (strengths and weaknesses). Data were collected through observation and focus group discussion. Data analysis in this study employs SWOT analysis and Analytic Hierarchy Process (AHP). SWOT analysis uses internal and competitiveness factors to reveal that the strategic position of the management is within the first quadrant (Strengths-Opportunities strategy) with the coordinate points of 0.76 and 2.52. Paired comparative evaluation with AHP reveals that the global priority value from strategic role groups is: PS1 (0.419) local government’s role, stakeholders, and institutional management; PS2 (0.239) research institutions’ role, research and development; PS3 (0.210) community and business world’s role; PS5 (0.136) regional condition and availability of raw materials’ role; and PS4 (0.131) institutional role and marketing system.